Teachers’ attitudes toward ICT integration in higher secondary education: evidence from Manipur, India - Ningchuiliu Gangmei; Kennedy Andrew Thomas (International Journal of Evaluation and Research in Education (IJERE), 2026)
One of the most basic imperatives in the current education system is the integration of information and communication technology (ICT) in education, and the teachers’ attitude is an important component for the successful integration of ICT. The aim of this study is to investigate the attitudes exhibited by the higher secondary school teachers with respect to the integration of ICT in the state of Manipur, India, and to examine the results with selected demographic variables. The study adopted a quantitative approach with a sample size of 1,100 teachers selected through proportionate stratified random sampling from government and private schools in Manipur using the attitude toward ICT scale (ATICT). The results show the positive existence of affective, cognitive, and behavioral attitudes among teachers towards the integration of ICT, and the results proved to be significantly valid among teachers from government schools, teachers with professional degrees, and mid-career teachers.